Quantitative spatial mapping of distorted state phases during the metal-insulator phase transition for nanoscale VO2 engineering - Yuichi Ashida; Takafumi Ishibe; Jinfeng Yang; Nobuyasu Naruse; Yoshiaki Nakamura (Science and Technology of Advanced Materials)
Vanadium dioxide (VO2) material, known for changing physical properties due to metal-insulator transition (MIT) near room temperature, has been reported to undergo a phase change depending on the strain. This fact can be a significant problem for nanoscale devices in VO2, where the strain field covers a large area fraction, spatially non-uniform, and the amount of strain can vary during the MIT process. Direct measurement of the strain field distribution during MIT is expected to establish a methodology for material phase identification. We have demonstrated the effectiveness of geometric phase analysis (GPA), high-resolution transmission electron microscopy techniques, and transmission electron diffraction (TED). The GPA images show that the nanoregions of interest are under tensile strain conditions of less than 0.4% as well as a compressive strain of about 0.7% (Rutile phase VO2[100] direction), indicating that the origin of the newly emerged TED spots in MIT contains a triclinic phase. This study provides a substantial understanding of the strain-temperature phase diagram and strain engineering strategies for effective phase management of nanoscale VO2.